Effect of Preoperative Zoledronic Acid Administration on Pain Intensity after Percutaneous Vertebroplasty for Osteoporotic Vertebral Compression Fractures. (3rd August 2020) - Hu, Weiran; Wang, Hongqiang; Shi, Xinge; Song, Yuepeng; Zhang, Guangquan; Xing, Shuai; Zhang, Kai; Gao, Yanzheng
Abstract : Introduction. This study aimed to compare and analyze the effect of preoperative zoledronic acid (ZOL) administration on pain intensity after percutaneous vertebroplasty (PVP) for osteoporotic vertebral compression fracture (OVCF). Methods . The study included 242 patients with OVCFs who underwent PVP in our hospital between January 2015 and June 2018. The patients were randomly assigned to either a ZOL group ( n = 121) or a control group ( n = 121). The patients in the ZOL group were treated preoperatively with intravenous infusion of 5 mg ZOL. Those in the control group were treated without ZOL. All the patients were followed up for 1 year. Results . No statistically significant differences in age, sex, weight, and body mass index (BMI) were found between the two groups. During the follow-up period, the visual analog scale score and Oswestry dysfunction index score in the ZOL group were lower than those in the control group. The bone mineral density at 6 or 12 months after treatment was significantly higher and the levels of the bone metabolism markers were significantly lower in the ZOL group than in the control group (P < 0.05 for both). Two patients in the treatment group had new vertebral fractures, whereas 13 patients in the control group had new vertebral fractures, which translate to recompression vertebral fracture incidence rates of 1.7% and 10.7%, respectively. The incidence rate of mild adverse reactions was significantly higher in the ZOL group than in the control group, but all the cases were endurable. Conclusion . Intravenous infusion of ZOL before PVP can effectively reduce postoperative pain intensity, reduce bone loss, increase bone density, reduce the risk of refracture, and improve patient quality of life.